2018
DOI: 10.1039/c8dt03619e
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the influence of ethylene group orientation on the iron(iii) spin state in the spin crossover complex [FeIII(Sal2-trien)]+

Abstract: The DFT calculations of the spin crossover complex [FeIII(Sal2-trien)]+ with different conformations of ethylene groups were performed. The results explain the presence of disordered structures/transition states of the ethylene groups observed in the [FeIII(Sal2-trien)]+-type structures found in the CCDC database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Such π-bonding is absent in 2 and the reversible SCO transition was observed at T sco = 118 K. The conformational changes in [Fe(III)(3-OMesal 2 -trien)] + at SCO were analyzed and it was shown at first time that reorientation of the central ethylene group of the trien occurs at the transition: it is near perpendicular to two side ethylene groups of the trien in the HS state and becomes near parallel to them in the LS state. This can be used as a very fast and visible indicator of the spin state in saltrien complexes [26]. It was also found that aging and subsequent thermocycling of the complex 2 led to a degradation of the spin-crossover transition.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Such π-bonding is absent in 2 and the reversible SCO transition was observed at T sco = 118 K. The conformational changes in [Fe(III)(3-OMesal 2 -trien)] + at SCO were analyzed and it was shown at first time that reorientation of the central ethylene group of the trien occurs at the transition: it is near perpendicular to two side ethylene groups of the trien in the HS state and becomes near parallel to them in the LS state. This can be used as a very fast and visible indicator of the spin state in saltrien complexes [26]. It was also found that aging and subsequent thermocycling of the complex 2 led to a degradation of the spin-crossover transition.…”
Section: Discussionmentioning
confidence: 94%
“…We have shown that different orientations of ethylene groups are energetically favorable for HS and LS complexes and therefore can be used as indicator of spin state of [Fe(III)(sal 2 trien)] + cations along with usual characteristics such as bond lengths and valent angles in the FeO 2 N 4 octahedron and α angle between salicylidene moieties [24,25]. The paper with detailed conformational analysis and density functional theory (DFT) calculations in the spin-crossover [Fe(III)(sal 2 trien)] + complexes will be published soon [26].…”
Section: [Fementioning
confidence: 99%
See 1 more Smart Citation
“…The obtuse dihedral angle α between two salicylidene groups of 3-OMe-Sal 2 trien of 94.39 (6) • also points to a high-spin state of the complex (Figure 5a). Besides, we have shown recently that different conformations of the trien moiety are energetically favorable for HS and LS complexes and can be used as an indicator of spin state of [Fe(III)(sal 2 trien)] + cations [10,25]. In 1, the central -CH 2 -CH 2 -bond (ii) of the trien is near-normal to the side bonds (i, iii) that is typical for the HS state ( Figure 5a and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Organic sublattice, in general, its intrinsic structural changes, as a component of the H-bonded network in the bulk of the hybrid, as well as the electronic structure of the acceptor molecule by itself, are capable of changing spin-states in SCO complexes. A combination of temperature and structure factors of the sublattices gives rise to polymorphic modifications, irreversibilities of the cooperative nature, such as spatially inhomogeneous phases (fractions) withing a single crystal [18][19][20][21][22][23][24][25][26]. Crystallographic identification of phase segregation is a hard task because "spin phases" are not new structures and do not necessarily have different symmetry.…”
Section: Introductionmentioning
confidence: 99%